The challenge of knowledge sharing practices of the Vietnamese science community in Ho Chi Minh city and the Mekong Delta - Bauer, Tatjana (ZEF development studies, 2011)
"In the Vietnamese science community, knowledge production and sharing are still limited. Based on intensive field work in South Vietnam, the author investigates how organizations operating in the field of water research understand and practice knowledge management. The national science policy, culture and tradition, international collaboration and local market forces all contribute to the current conditions of knowledge exchange in Vietnam. It is shown that the concentration of organizations in 'knowledge clusters' could possibly increase the innovative capacity of R&D whch represents a key driving force in the country's ambitious plans of becoming a middle income country."--Publisher's description.